Câu 22 trang 29 Sách bài tập (SBT) Toán 8 tập 1

Cho hai biểu thức:

A =\({1 \over x} + {1 \over {x + 5}} + {{x - 5} \over {x\left( {x + 5} \right)}}\)

B =\({3 \over {x + 5}}\)

Chứng tỏ rằng A = B

Giải:

A \( = {1 \over x} + {1 \over {x + 5}} + {{x - 5} \over {x\left( {x + 5} \right)}} = {{x + 5} \over {x\left( {x + 5} \right)}} + {x \over {x\left( {x + 5} \right)}} + {{x - 5} \over {x\left( {x + 5} \right)}}\)

\( = {{x + 5 + x + x - 5} \over {x\left( {x + 5} \right)}} = {{3x} \over {x\left( {x + 5} \right)}} = {3 \over {x + 5}}\)

Vậy A = B

Các bài cùng chủ đề